Developing resource-informed strategic assessments and recommendations - Davis, Paul K., 1943-; Johnson, Stuart E., 1944-; Long, Duncan; Gompert, David C.; Rand eBooks (Santa Monica, CA : RAND, 2008)
A debate will likely occur in 2009 about U.S. global national-security strategy. The authors describe and illustrate a methodology to help frame and evaluate resource-informed strategies. The core is an integrated portfolio-analysis approach that compares options by their anticipated effectiveness, risks, and resource implications--all three of which are multifaceted. The approach deals explicitly with both uncertainty and differences of strategic perspective. Three illustrative grand strategies are compared, which deal in different ways with the problems of our time, which include terrorism and more classic long-term strategic considerations such as general deterrence and competition.
Introduction -- The Operating-Unit Perspective -- Characterizing Alternative Strategies in Terms of Implications for Operating Units (COCOMs) -- Application to Some Illustrative Strategies -- Integrated Portfolio Analysis of Illustrative Strategies -- Conclusions -- Appendix A: Responsibilities of the Chairman of the Joint Chiefs of Staff -- Appendix B: The Portfolio Analysis Tool -- Appendix C: A Tool for Customized Reporting -- Appendix D: Documentation of Cost Estimates -- Appendix E: Treatment of Risks.
"RAND National Defense Research Institute."
This research was conducted in the RAND National Defense Research Institute"--p. [ii].
Includes bibliographical references (p. 157-164).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Department of Defense -- Planning; Military planning -- United States; National security -- United States -- 21st century; Resource allocation -- United States; Strategy; United States -- Defenses; United States -- Military policy; United States -- Strategic aspects; Electronic books